KOMPETENSI, DISIPLIN KERJA, KUALITAS PELAYANAN DAN KEPUASAN MASYARAKAT - Kiswanto, Alfa Riandi Anwar Meyzi Heriyanto, (Jurnal Ilmu Administrasi Negara, 2020)
Competence, Work Discipline, Service Quality, People Satisfaction. The purpose of this study is to determine the Effect of Competence and Work Discipline on People Satisfaction with Service Quality as an intervening variable At the Tenayan Raya Local Government. This research uses Path Analysis Method using primary data. The data used in this study were obtained from 113 unique respondents that had joined “Gerakan Indonesia Sadar Admindukcapil (GISA)” phase one and two. This study concluded that Work Discipline were statistically significance affect Service Quality. However, there is no significant relation between Competence and Service Quality. Competence, Work Discipline and Service Quality were statistically significance affect People Satisfaction.